Development of a qualified clinical data registry for emergency medicine. Issue 6 (21st December 2021) - Epstein, Stephen K.; Griffey, Richard T.; Lin, Michelle P.; Augustine, James J.; Goyal, Pawan; Venkatesh, Arjun K.
Abstract: The passage of the Medicare Access and CHIP Reauthorization Act (MACRA) in 2015 marked a fundamental transition in physician payment by the Centers for Medicare and Medicaid Services (CMS) from traditional fee‐for service to value‐based models. MACRA led to the creation of the CMS Quality Payment Program (QPP), which bases the value of physician care in large part on physician quality reporting. The QPP enabled a shift away from legacy CMS‐stewarded quality measures that had limited applicability to individual specialties toward specialty‐specific quality measures developed and stewarded by physician specialty societies using Qualified Clinical Data Registries (QCDRs). This article describes the development of the first nationally available emergency medicine QCDR as a means for emergency physicians to participate in the QPP, measure, and benchmark emergency physician quality.